Phishing via instant messaging systems on social media sites using artificial intelligence techniques in the field of social engineering - علي, مجد (Latakia University Journal -Engineering Sciences Series, 2024)
Phishing is an example of a very effective form of cybercrime that enables criminals to deceive users and steal sensitive data. With the increasing growth of Internet users, especially on social media platforms, the amount of publicly available personal information has increased dramatically, making these users more vulnerable to phishing attacks. This article provides a detailed explanation of the modern technical methods used in such attacks, especially the use of Natural Language Processing techniques for topic classification of social media posts to determine the victim’s area of interest and form the base for launching an attack that aims to steal victim’s sensitive data by sending a customized message according to His field of interest using instant messaging systems.